2018
DOI: 10.1007/s10198-018-0986-y
|View full text |Cite
|
Sign up to set email alerts
|

The economic burden of disease of epithelial ovarian cancer in Spain: the OvarCost study

Abstract: EOC imposes a significant economic burden on the national healthcare system and society in Spain. Investment in better early diagnosis techniques might increase survival and patients' quality of life. This would likely reduce costs derived from late stages, consequently leading to a substantial reduction of the economic burden associated with EOC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 33 publications
1
14
0
1
Order By: Relevance
“…Gordon et al reported that in women with primary epithelial ovarian cancer, treatment costs increased with later stage at diagnosis and more than one lines of chemotherapy [17]. Similar results were reported by Delgado-Ortega et al using Markov models to simulate cohorts of women with epithelial ovarian cancer in Spain [18]. Using health economic models, Rocconi et al showed that the incremental cost-effectiveness ratio was not favorable after the second line of chemotherapy in patients with platinum resistant epithelial ovarian cancer [19].…”
supporting
confidence: 53%
“…Gordon et al reported that in women with primary epithelial ovarian cancer, treatment costs increased with later stage at diagnosis and more than one lines of chemotherapy [17]. Similar results were reported by Delgado-Ortega et al using Markov models to simulate cohorts of women with epithelial ovarian cancer in Spain [18]. Using health economic models, Rocconi et al showed that the incremental cost-effectiveness ratio was not favorable after the second line of chemotherapy in patients with platinum resistant epithelial ovarian cancer [19].…”
supporting
confidence: 53%
“…Genetic testing to HGEOC patients allows registering patients with hereditary cancer that may transmit gBRCA1/2m to their descendants, and, therefore, may be useful for designing effective public health programmes against cancer to the target population. As was shown in the Ovarcost study, investing in techniques for early diagnosis may imply higher survival rates and a substantial reduction in the economic burden of cancer, due to possible cost savings at advanced disease stages [26]. It is worth noting that if all gBRCA1/2m carriers accepted to undergo RRS, the number of BC and EOC patients would be decreased and that the ICUR of the germline BRCA1/2 testing would be lower than our base-case result (€31,621.33/QALY).…”
Section: Discussionmentioning
confidence: 95%
“…It should also be noted that the simulation did not consider other benefits that germline BRCA1/2 testing may have on patients, such as providing information on the most appropriate therapy choice [9]. Besides, healthy gBRCA1/2m carriers who choose not to undergo RRS would still receive surveillance visits and tests that may imply higher benefits like earlier diagnosis of cancer, which may turn out in higher overall and disease-free survival rates [9,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have attempted to estimate the costs of cancer on a population level but these were either for the short term [9,55,56] and/or focused on selected type/s of cancer [8,[57][58][59][60][61][62][63][64]. For example, Luengo-Fernandez et al [55] performed a population-based cost analysis for breast, colorectal, lung and prostate cancer across the European Union (27 countries) from a societal perspective, including healthcare costs, informal care costs and productivity losses.…”
Section: Discussionmentioning
confidence: 99%